Green Human Resource Management: A Comprehensive Analysis of Practices, Impacts, and Future Directions - Dyah Palupiningtyas; Sri Mulyani Wahono (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This article is a systematic literature review that investigates the impact and role of Green Human Resource Management (GHRM) in organizational performance and sustainability. By detailing the findings from 18 related studies, this article discusses the role of GHRM in motivating environmentally friendly behavior among employees and its impact on organizational performance and sustainability. The article's background discusses the urgency of GHRM in responding to global sustainability challenges and enhancing sustainable human resource management practices. The literature review involves a deep understanding of the impact of GHRM on variables such as employee behavior, green innovation, and organizational performance. The research methods include the selection of relevant studies, qualitative data analysis, and the synthesis of these findings. The article's discussion highlights significant findings, such as the positive influence of GHRM on employee green behavior and environmental innovation, as well as its contribution to organizational sustainability. Practical implications involve guidelines for implementing GHRM in organizations, while theoretical implications enrich our understanding of GHRM's role in sustainable human resource management. The conclusion of the article provides a comprehensive overview of the relationship between GHRM and organizational performance and sustainability. Further research recommendations include identifying knowledge gaps and future research opportunities to deepen our understanding of GHRM. This article is expected to contribute to related literature and provide valuable guidance for research and GHRM implementation in various organizational contexts.